ANALISIS KESULITAN BAHASA INDONESIA BAGI PEMELAJAR DI SAMSIFL UZBEKISTAN PADA EMPAT KETERAMPILAN BERBAHASA - Jamaluddin Nasution (Balai Bahasa Sumatera Utara, 2019)
The difficulties faced by students vary, such as intelligence and non-intelligence factors. This study is to know; (1) what the most difficult language skills, (2) the reasons of students at the difficulties in the language skills, and (3) how the students face their difficulties. The method of this study is descriptive, conducted in ILFS class of English and Translation Program at SAMSIFL (Samarkand State Institute of Foreign Languages) Uzbekistan. The result are listening (61.68), speaking (69.07), writing (71.89), and reading (76.29). Result of questionnaires; students like Indonesian language (85.71%), the Indonesian pronunciation (65.71%), symbols/letters is not different (80.00%), no difficulty in uttering Indonesian language words (77.14%), good and helpful guidance book (91.43%), speaker speaks fast (97.14%), difficulties in listening (94.29%), no difficulty in reading (85.71%), no difficulty in writing (80.00%), difficulty in speaking (71.43%), most liked language skills is reading (57.14%), most hated language skills is listening (94.29%), most difficult language skills is listening (88.57%), easiest language skills is reading (71.43%), and the students’ action facing the difficulties is asking the teacher (85.71%). It is expected that the ILFS teaching concerns on students’ difficulties firstly and give motivation during the teaching process.